Korelasi antara Dzikir dan Ketenangan Hati (Tinjauan I’jazul Ilmi pada Q.S. Al Ra’d Ayat 28) - Vanilla, Puspa; Cahyo, Agung; Lubis, Alex Connery (TSAQOFAH, 2024)
This research examines, researches and analyzes a context of the role of dhikr in peace of mind, in Q.S. Ar ra'd verse 28. The focus of this research is more on a scientific research approach to the influence of dhikr with peace of mind as stated in this verse. This research uses qualitative methods, analysis with literature review to reveal scientific theories related to the influence of dhikr on peace of mind from several previous studies. Based on the verse studied, it states that I'jaz 'ilmi related to this verse, produces several findings. (1). Dhikr plays a very important role in calming a person's heart and soul. (2) Dhikr is also often used as mental health therapy and to relieve pain that occurs in sick sufferers. This is because the activity of dhikr will stimulate our body to release endorphins, which can create calm in a person's heart and soul.